Sheet provided with heat-insulating layer and pressure-sensitive adhesive layer

By combining the thermal insulation layer and the pressure-sensitive adhesive layer in the sheet, and adjusting their strength relationship after a specific thermal history, the problem of insufficient peelability of the thermal insulation material in the reflow soldering process is solved, and excellent peelability and product quality are achieved .

CN119343421APending Publication Date: 2025-01-21RESONAC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380037151.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-21
Filing Date
2023-06-14
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the reflow welding process, the peelability of the thermal insulation material is insufficient, resulting in the pressure-sensitive adhesive layer remaining on the side of the bonded body, affecting product quality.

Method used

By combining the thermal insulation layer and the pressure-sensitive adhesive layer in the sheet, and after a specific thermal history, the overall strength of the thermal insulation layer is greater than the 90° peel strength of the pressure-sensitive adhesive layer to improve the peelability after the reflow soldering process. .

Benefits of technology

It achieves excellent peelability after the reflow soldering process, ensuring complete peeling of the insulation material, avoiding residues, and improving product quality and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343421A_ABST
    Figure CN119343421A_ABST
Patent Text Reader

Abstract

The sheet is provided with a heat insulating layer and a pressure-sensitive adhesive layer, and the overall strength of the heat insulating layer after a thermal history in which the temperature is increased from 25 DEG C to 200 DEG C at a temperature increase rate of 47 DEG C / min and then is increased from 200 DEG C to 260 DEG C at a temperature increase rate of 38 DEG C / min is greater than the 90 DEG peel strength of the pressure-sensitive adhesive layer after the thermal history has been applied.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a sheet material having a heat insulating layer and a pressure-sensitive adhesive layer. Background Art

[0002] Non-volatile memory, which features low power consumption and high-speed read / write, has attracted much attention as a next-generation memory. For example, phase change memory (PCM), magnetoresistive RAM (MRAM), resistive random access memory (ReRAM), etc. are known. Non-volatile memory is not heat-resistant, and quality maintenance when exposed to high temperature environments during the reflow soldering process during installation has become an issue.

[0003] In response to this issue, for example, patent document 1 discloses a method for manufacturing a magnetic recording device, which includes a reflow process, and the reflow process includes: a first step of providing an insulating material on the surface of the magnetic recording device exposed in a reflow furnace; a second step of passing the magnetic recording device provided with the insulating material through the reflow furnace and heating the magnetic recording device; and a third step of removing the insulating material from the heated magnetic recording device.

[0004] Previous technical literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-224663 Summary of the invention

[0007] Technical issues to be solved by the invention

[0008] The inventors of the present invention have studied the use of a sheet having an insulating layer and a pressure-sensitive adhesive layer as the insulating material as described above. When such an insulating material is used, the insulating material is disposed on the adherend by making the pressure-sensitive adhesive layer pressure-sensitively adhere to the adherend (magnetic recording device), but when the insulating material is peeled off from the adherend after the reflow process, the pressure-sensitive adhesive layer may not be peeled off together with the insulating layer and remain on the adherend side (for example, peeling occurs between the layers constituting the insulating material). Therefore, it is preferred to use an insulating material having excellent peelability so that the pressure-sensitive adhesive layer does not remain on the adherend side when peeled off after the reflow process.

[0009] Therefore, an object of one aspect of the present invention is to provide a sheet suitable for a thermal insulation material having excellent releasability after a reflow process.

[0010] Means for solving technical problems

[0011] Through the research of the present inventors, it is clear that if the sheet is to be peeled off from the adherend after the reflow process by combining the heat insulating layer and the pressure sensitive adhesive layer, sometimes the pressure sensitive adhesive layer will not be peeled off together with the heat insulating layer and will remain on the adherend side. The present inventors further conducted in-depth research and found that in a sheet having a heat insulating layer and a pressure sensitive adhesive layer, the peelability after the reflow process can be improved by making the overall strength of the heat insulating layer after the reflow process greater than the 90° peel strength of the pressure sensitive adhesive layer after the reflow process. The present invention provides the following [1] to [3] in several aspects.

[0012] [1] A sheet comprising a heat insulating layer and a pressure-sensitive adhesive layer, wherein the overall strength of the heat insulating layer after a heat history of heating from 25°C to 200°C at a heating rate of 47°C / min and then from 200°C to 260°C at a heating rate of 38°C / min is greater than the 90° peel strength of the pressure-sensitive adhesive layer after the heat history.

[0013] [2] The sheet according to [1], which is used as a heat insulating material in a reflow process when manufacturing a semiconductor device.

[0014] [3] A method for manufacturing a semiconductor device, comprising: a step of configuring the sheet described in [1] or [2] on the semiconductor device; a step of reflowing the semiconductor device on which the sheet is configured; and a step of peeling the sheet from the semiconductor device.

[0015] Effects of the Invention

[0016] According to the present invention, it is possible to provide a sheet suitable for a heat insulating material having excellent releasability after a reflow process. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a schematic cross-sectional view showing one embodiment of a sheet.

[0018] Figure 2 It is a schematic cross-sectional view showing one embodiment of the arrangement step.

[0019] Figure 3 It is a schematic cross-sectional view showing another embodiment of the arrangement step.

[0020] Figure 4 It is a schematic cross-sectional view showing another embodiment of the arrangement step.

[0021] Figure 5 It is a schematic cross-sectional view showing another embodiment of the arrangement step. DETAILED DESCRIPTION

[0022] Hereinafter, embodiments of the present invention will be described in detail. However, the present invention is not limited to the following embodiments.

[0023] The term "(meth)acryloyl" in the present specification refers to "acryloyl" and its corresponding "methacryloyl", and the same also applies to "(meth)acrylate", "(meth)acrylic acid" and the like.

[0024] The weight average molecular weight (Mw) in this specification refers to a value measured by gel permeation chromatography (GPC) under the following conditions using polystyrene as a standard substance.

[0025] ·Measurement equipment: HLC-8320GPC (product name, manufactured by TOSOH CORPORATION)

[0026] Analytical column: TSKgel SuperMultipore HZ-H (3 connected) (product name, manufactured by TOSOH CORPORATION)

[0027] Guard column: TSKguardcolumn SuperMP(HZ)-H (product name, manufactured by TOSOH CORPORATION)

[0028] Eluent: THF

[0029] ·Measurement temperature: 25℃

[0030] <Sheet>

[0031] Figure 1 This is a schematic cross-sectional view showing one embodiment of a sheet. Figure 1 The sheet material 100 shown has a heat insulating layer 101 and a pressure sensitive adhesive layer 102. The heat insulating layer 101 and the pressure sensitive adhesive layer 102 can be stacked in contact with each other. In the sheet material 100, the overall strength of the heat insulating layer 101 after applying a predetermined heat history and the 90° peel strength of the pressure sensitive adhesive layer 102 satisfy a specific relationship.

[0032] Specifically, the overall strength of the heat insulating layer 101 after applying a thermal history (hereinafter, this thermal history is also referred to as a "specific thermal history") of heating from 25°C to 200°C at a heating rate of 47°C / min and then heating from 200°C to 260°C at a heating rate of 38°C / min is greater than the 90° peel strength of the pressure sensitive adhesive layer 102 after the specific thermal history is applied. Usually, in the reflow process, the reflow furnace is heated to about 260°C in stages. The sheet 100 has the heat insulating layer 101 and the pressure sensitive adhesive layer 102 such that the overall strength of the heat insulating layer 101 in the sheet 100 and the 90° peel strength of the pressure sensitive adhesive layer 102 satisfy the above-mentioned size relationship, and the peelability of the sheet 100 after the reflow process becomes good.

[0033] In this specification, the overall strength of the heat insulating layer 101 refers to the magnitude of the force required to break the heat insulating layer 101 at 25° C. with the incision being the starting point when the incision is provided in a direction perpendicular to the thickness direction of the heat insulating layer 101. The overall strength of the heat insulating layer 101 can be measured, for example, using a tensile tester and by the method described in the examples.

[0034] In this specification, the 90° peel strength of the pressure-sensitive adhesive layer 102 refers to the magnitude of the force required to peel the pressure-sensitive adhesive layer 102 along a 90° direction at 25° C. when the pressure-sensitive adhesive layer 102 is attached to a Si wafer. The peel strength of the pressure-sensitive adhesive layer 102 is measured, for example, by a tensile tester and by the method described in the Examples.

[0035] In addition, the overall strength of the heat insulating layer 101 and the 90° peel strength of the pressure sensitive adhesive layer 102 are measured after the heat insulating layer 101 and the pressure sensitive adhesive layer 102 are naturally cooled to 25° C. after a specific heat history is applied to the heat insulating layer 101 and the pressure sensitive adhesive layer 102. The temperature of the natural cooling environment is arbitrary, but in one embodiment, the heat insulating layer 101 and the pressure sensitive adhesive layer 102 can be naturally cooled to 60° C. in an environment of 60° C., and then naturally cooled to 25° C. in an environment of 25° C.

[0036] The difference between the overall strength of the insulation layer 101 after applying a specific thermal history and the 90° peel strength of the pressure-sensitive adhesive layer 102 ((overall strength of the insulation layer 101) - (90° peel strength of the pressure-sensitive adhesive layer 102)) can be, for example, greater than 10 N / m or greater than 20 N / m, or less than 400 N / m or less than 300 N / m.

[0037] The overall strength of the heat insulating layer 101 after a specific heat history is applied may be, for example, 30 N / m or more, 50 N / m or more, or 500 N / m or less.

[0038] The 90° peel strength of the pressure-sensitive adhesive layer 102 after applying a specific heat history may be, for example, 5 N / m or more, or 300 N / m or less, or 200 N / m or less.

[0039] The heat insulating layer 101 is a layer having heat insulating properties, and any layer has to have overall strength satisfying the above conditions. The heat insulating layer 101 preferably has a thermal conductivity of 100 mW / (m·K) or less, 90 mW / (m·K) or less, or 80 mW / (m·K) or less at 25°C.

[0040] The material of the heat-insulating layer 101 is not particularly limited. The heat-insulating layer 101 can be a layer composed of a porous material. The porous material can be an organic porous material or an inorganic porous material. As an example of an organic porous material, a resin porous material can be cited. As an example of a resin porous material, a melamine resin porous material (melamine sponge), a polyimide resin porous material (polyimide foam) and a polyaramid resin porous material (polyaramid felt) can be cited. As an example of an inorganic porous material, a carbon porous material and a glass porous material can be cited. As an example of a carbon porous material, a carbon felt can be cited. As an example of a glass porous material, glass fiber paper and glass felt can be cited.

[0041] The heat insulating layer 101 may be a layer containing hollow particles. Hollow particles are particles having an outer shell and a hollow portion. Hollow particles may be organic hollow particles whose outer shells are composed of organic materials, or inorganic hollow particles whose outer shells are composed of inorganic materials. Hollow particles may include any one of organic hollow particles and inorganic hollow particles, or may include both.

[0042] As the organic hollow particles, there can be mentioned first hollow particles which are heat-expandable organic hollow particles and second hollow particles which are organic hollow particles other than the first hollow particles. The organic hollow particles may include either or both of the first hollow particles and the second hollow particles, and preferably include both of the first hollow particles and the second hollow particles.

[0043] The first hollow particles are organic hollow particles that expand due to heat (heat-expandable). The heat-expandable organic hollow particles in this specification refer to organic hollow particles whose maximum volume expansion ratio relative to the volume at 25°C is 10 times or more. In the case where the thermal insulation layer 101 contains the first hollow particles, even if a phenomenon occurs in the reflow process that acts in a direction that reduces the thermal insulation of the thermal insulation layer 101 (for example, even if the second hollow particles described later shrink and the volume of the hollow portion decreases), the first hollow particles will expand due to heat, which contributes to the increase in the volume of the thermal insulation hollow portion of the thermal insulation layer 101. Therefore, the reduction in the thermal insulation of the thermal insulation layer 101 (sheet 100) can be suppressed.

[0044] The maximum volume expansion ratio of the first hollow particle is measured by thermomechanical analysis (TMA) as the ratio of the maximum volume of the first hollow particle when the temperature is increased at a temperature increase rate of 10° C. / min to the volume at 25° C. (maximum volume / volume at 25° C.). The maximum volume expansion ratio of the first hollow particle may be, for example, 20 times or more, 30 times or more, or 40 times or more, or 120 times or less.

[0045] The shell of the first hollow particle is preferably composed of a polymer, and is further preferably composed of a thermoplastic polymer. At this time, since the shell softens due to heating, even if the liquid contained in the hollow portion is gasified and the internal pressure rises, the hollow particle is not easy to break and is easy to expand. Thermoplastic polymers can be, for example, polymers containing acrylonitrile, vinylidene chloride, etc. as monomer units. The thickness of the shell can be more than 2 μm, or less than 15 μm.

[0046] The hollow portion of the first hollow particle, for example, contains a liquid. The first hollow particle, for example, contains a liquid at normal temperature and pressure (for example, at least at atmospheric pressure and 30°C). The liquid is appropriately selected, for example, according to the heating temperature in the reflow process and the shrinkage start temperature of the second hollow particle described later. The liquid is, for example, a liquid that vaporizes at a temperature below the highest heating temperature in the reflow process. The liquid can be a liquid that vaporizes at a temperature below the shrinkage start temperature of the second hollow particle. The liquid can be, for example, a hydrocarbon having a boiling point (under atmospheric pressure) of 50°C or more, 100°C or more, 150°C or more, or 200°C or more. In addition to the above-mentioned liquid, the hollow portion of the first hollow particle may also contain a gas.

[0047] As the components contained in the hollow part of the first hollow particle, for example, there can be mentioned hydrocarbons such as propane, propylene, butene, n-butane, isobutane, n-pentane, isopentane, neopentane, n-hexane, isohexane, heptane, isooctane, n-octane, isoalkanes (carbon number: 10 to 13), and petroleum ether; low boiling point compounds such as methane halides and tetraalkylsilane; and compounds that are gasified by thermal decomposition such as azodicarbonamide.

[0048] The average particle size of the first hollow particles may be 5 μm or more, 10 μm or more, or 50 μm or less, 40 μm or less, or 30 μm or less. The average particle size of the first hollow particles is measured by a laser diffraction / scattering method (for example, using “SALD-7500nano” manufactured by SHIMADZU CORPORATION).

[0049] From the viewpoint that the sheet 100 is more preferably used as an insulating material in a reflow soldering process (usually heated to 260°C), the expansion start temperature of the first hollow particle is preferably below the contraction start temperature of the second hollow particle described later. The expansion start temperature of the first hollow particle is preferably above 150°C or above 180°C, and preferably below 260°C, below 240°C, below 220°C or below 200°C. The expansion start temperature of the first hollow particle refers to the temperature of the intersection of the tangent of the point where a volume change of more than 3 times / 5°C is produced and the straight line (horizontal axis) where the volume change is zero (initial volume) in the curve of temperature (horizontal axis)-volume change (vertical axis) when the temperature is increased at a heating rate of 10°C / min by thermomechanical analysis (TMA).

[0050] From the viewpoint that the sheet 100 is more preferably used as an insulating material in the reflow process, the maximum expansion temperature of the first hollow particles is preferably 100° C. or more, 150° C. or more, 200° C. or more, or 210° C. or more, and preferably 290° C. or less, 280° C. or less, or 270° C. or less. The maximum expansion temperature of the first hollow particles refers to the temperature at which the first hollow particles exhibit the above-mentioned maximum volume expansion ratio.

[0051] From the viewpoint of preventing the thermal insulation properties of the sheet 100 from decreasing, the content of the first hollow particles (the content at atmospheric pressure and 30°C. The same applies hereinafter) is preferably 1 mass % or more, more preferably 2 mass % or more, further preferably 4 mass % or more, particularly preferably 5 mass % or more, and can be less than 20 mass % or less than 15 mass %.

[0052] From the viewpoint of preventing the thermal insulation of the sheet 100 from decreasing, the content of the first hollow particles is preferably 0.5% by volume or more, more preferably 1.0% by volume or more, and further preferably 1.5% by volume or more, based on the total volume of the thermal insulation layer 101. From the viewpoint of suppressing excessive expansion of the volume of the sheet 100, the content of the first hollow particles may be 10% by volume or less, 7% by volume or less, 5% by volume or less, or 4% by volume or less, based on the total volume of the thermal insulation layer 101.

[0053] The second hollow particles are organic hollow particles other than the first hollow particles. That is, the second hollow particles are organic hollow particles whose maximum volume expansion ratio relative to the volume at 25° C. is less than 10 times. By using the second hollow particles, the thermal insulation of the insulation layer 101 is improved, and the sheet 100 can be more appropriately used as an insulation material. The maximum volume expansion ratio of the second hollow particles is measured by the same method as the maximum volume expansion ratio of the first hollow particles.

[0054] The shell of the second hollow particle is composed of an organic material. The shell of the second hollow particle is preferably composed of a polymer, more preferably composed of a thermoplastic polymer. In this case, the hollow particles are not easily broken even if pressurized, and the hollow structure can be maintained, so it is easy to maintain the thermal insulation of the sheet 100. Thermoplastic polymers can be, for example, polymers containing acrylonitrile, vinylidene chloride, etc. as monomer units. The thickness of the shell can be more than 0.005 μm, or less than 15 μm.

[0055] The hollow part of the second hollow particle contains, for example, a gas. The second hollow particle contains, for example, a gas at normal temperature and pressure (for example, at least at atmospheric pressure and 30° C.). The hollow part of the second hollow particle may contain a liquid in addition to a gas.

[0056] As the components contained in the hollow part of the second hollow particle, for example, there can be mentioned hydrocarbons such as propane, propylene, butene, n-butane, isobutane, n-pentane, isopentane, neopentane, n-hexane, isohexane, heptane, isooctane, n-octane, isoalkanes (carbon number: 10 to 13), petroleum ether, etc.; low boiling point compounds such as methane halides and tetraalkylsilane; decomposition products of compounds gasified by thermal decomposition of azodicarbonamide, etc. In addition, the component contained in the hollow part of the second hollow particle may be air.

[0057] From the viewpoint of improving thermal insulation, the average particle size of the second hollow particles is preferably 150 μm or less, more preferably 120 μm or less, further preferably 100 μm or less, for example, 5 μm or more, 10 μm or more, 20 μm or more, or 30 μm or more. The average particle size of the second hollow particles is measured by laser diffraction / scattering method (for example, using "SALD-7500nano" manufactured by SHIMADZU CORPORATION).

[0058] The density of the second hollow particle can be 500 kg / m 3 Below, 300kg / m 3 Below, 100kg / m 3 Below, 50kg / m 3 Below or 40kg / m 3 Below, can also be 10kg / m 3 Above or 20kg / m 3 The density of the second hollow particle in this specification refers to the density measured by the tap density method. That is, the second hollow particle (about 5 g) is put into a 10 mL measuring cylinder and tapped 50 times, and the volume when the top is stable is taken as the stable volume and the density is calculated using the following formula.

[0059] Density = initial input (kg) / volume at stable state (m 3 )

[0060] From the viewpoint that the sheet 100 is more preferably used as an insulating material in a reflow process (generally heated to 260° C.), the shrinkage start temperature of the second hollow particles is preferably 150° C. or more, 170° C. or more, or 180° C. or more, and may be 260° C. or less, 240° C. or less, 220° C. or less, or 200° C. or less. The shrinkage start temperature of the second hollow particles refers to the temperature at which the volume change reaches a maximum value in a curve of temperature (horizontal axis)-volume change (vertical axis) when the temperature is increased at a heating rate of 10° C. / min by thermomechanical analysis (TMA).

[0061] From the viewpoint of improving the thermal insulation properties of the sheet 100, the content of the second hollow particles (the content at atmospheric pressure and 30°C. The same applies hereinafter) is preferably 1 mass % or more, more preferably 3 mass % or more, further preferably 5 mass % or more, for example, can be 20 mass % or less, based on the total mass of the thermal insulation layer 101.

[0062] From the viewpoint of improving the thermal insulation of the sheet 100 , the content of the second hollow particles is preferably 50% by volume or more, more preferably 60% by volume or more, and for example may be 95% by volume or less, based on the total volume of the thermal insulation layer 101 .

[0063] The mass ratio of the content of the second hollow particles relative to the content of the first hollow particles (the content (mass) of the second hollow particles / the content (mass) of the first hollow particles) is preferably 1 / 5 or more, more preferably 1 / 3 or more. The mass ratio of the content of the second hollow particles relative to the content of the first hollow particles is preferably 3 or less, more preferably 2 or less, and further preferably 1 or less.

[0064] The volume ratio of the content of the second hollow particles to the content of the first hollow particles (content (volume) of the second hollow particles / content (volume) of the first hollow particles) is preferably 10 or more, more preferably 15 or more. The volume ratio of the content of the second hollow particles to the content of the first hollow particles is preferably 80 or less, more preferably 60 or less, and further preferably 45 or less.

[0065] The inorganic material constituting the shell of the inorganic hollow particle can be, for example, borosilicate glass (sodium borosilicate glass, etc.), aluminosilicate glass, or inorganic glass such as glass obtained by compounding them. The hollow portion of the inorganic hollow particle contains, for example, a gas. The inorganic hollow particle contains a gas at room temperature and pressure (for example, at least at atmospheric pressure and 30° C.).

[0066] Based on the total mass of the insulating layer 101, the content of the inorganic hollow particles (content at atmospheric pressure and 30°C. The same applies hereinafter) is preferably 20 mass % or more, more preferably 22 mass % or more, further preferably 25 mass % or more, and can be 40 mass % or less or 30 mass % or less.

[0067] Based on the total volume of the heat insulating layer 101 , the content of the inorganic hollow particles is preferably 55 volume % or more, more preferably 60 volume % or more, further preferably 63 volume % or more, and may be 80 volume % or less or 75 volume % or less.

[0068] Based on the total mass of the sheet 100, the total content of the hollow particles (the total content of the first hollow particles, the second hollow particles and the inorganic hollow particles at atmospheric pressure and 30°C. The same applies below) can be, for example, greater than 4 mass%, greater than 8 mass% or greater than 10 mass%, or less than 40 mass%, less than 35 mass% or less than 30 mass%.

[0069] The total content of the hollow particles may be, for example, 50% by volume or more, 60% by volume or more, or 70% by volume or more, or 95% by volume or less, based on the total volume of the sheet 100 .

[0070] When the heat insulating layer 101 contains hollow particles, the heat insulating layer 101 preferably further contains a matrix polymer. The matrix polymer is a polymer (binder polymer) that becomes a matrix (forms a continuous phase) for holding other materials such as hollow particles contained in the heat insulating layer 101. The hollow particles may be held in the matrix polymer or may be dispersed in the matrix polymer.

[0071] The matrix polymer may contain a compound represented by the following formula (1) as a monomer unit. In other words, the matrix polymer may be a polymer of a polymerizable compound containing a compound represented by the following formula (1).

[0072]

[0073] In formula (1), R 11 and R 12 Each independently represents a hydrogen atom or a methyl group, R 13 It represents a divalent group having a polyoxyalkylene chain.

[0074] When the matrix polymer contains the compound represented by the above formula (1) as a monomer unit, the heat insulating layer 101 has low elasticity and excellent elongation, and thus the followability of the sheet 100 to the adherend can be improved.

[0075] In one embodiment, R 11 and R 12 In another embodiment, one of R may be a hydrogen atom and the other may be a methyl group. 11 and R 12 Both of them can be hydrogen atoms. In other embodiments, R 11 and R 12 Both of these may be methyl groups.

[0076] In one embodiment, the polyoxyalkylene chain includes a structural unit represented by the following formula (2). This can improve the strength of the heat insulating layer 101.

[0077]

[0078] At this time, R 13 It may be a divalent group having a polyoxyethylene chain, and the compound represented by the formula (1) is preferably a compound represented by the following formula (1-2) (polyethylene glycol di(meth)acrylate).

[0079]

[0080] In formula (1-2), R 11 and R 12 The meanings of are respectively the same as R in formula (1) 11 and R 12 has the same meaning as , and m is an integer greater than 2.

[0081] In another embodiment, the polyoxyalkylene chain includes a structural unit represented by the following formula (3).

[0082]

[0083] At this time, R 13 It may be a divalent group having a polyoxypropylene chain, and the compound represented by the formula (1) is preferably a compound represented by the following formula (1-3) (polypropylene glycol di(meth)acrylate).

[0084]

[0085] In formula (1-3), R 11 and R 12 The meanings of are respectively the same as R in formula (1) 11 and R 12 has the same meaning as , and n is an integer greater than 2.

[0086] In another embodiment, the polyoxyalkylene chain is preferably a copolymer chain comprising the structural unit represented by the above formula (2) and the structural unit represented by the formula (3). The copolymer chain may be any of an alternating copolymer chain, a block copolymer chain or a random copolymer chain. The copolymer chain is preferably a random copolymer chain.

[0087] In each of the above embodiments, the polyoxyalkylene chain may have, as a structural unit, an oxyalkylene group having 4 to 5 carbon atoms such as an oxymethylene group, an oxybutylene group, or an oxypentylene group, in addition to the structural unit represented by formula (2) and the structural unit represented by formula (3).

[0088] R 13 It may be a divalent group having other organic groups in addition to the above-mentioned polyoxyalkylene chain. Other organic groups may be chain groups other than the polyoxyalkylene chain, for example, a methylene chain (a chain with -CH2- as a structural unit), a polyester chain (a chain containing -COO- in a structural unit), a polyurethane chain (a chain containing -OCON- in a structural unit), etc.

[0089] For example, the compound represented by formula (1) may be a compound represented by the following formula (1-4).

[0090]

[0091] In formula (1-4), R 11 and R 12 The meanings of are respectively the same as R in formula (1) 11 and R 12 has the same meaning, R 14 and R 15 Each of k1, k2 and k3 is independently an alkylene group having 2 to 5 carbon atoms, and each of k1, k2 and k3 is independently an integer greater than 2. For example, k2 may be an integer less than 16.

[0092] There are multiple R 14 and R 15 They may be the same or different from each other. 14 and R 15 Preferably, they contain ethylene and propylene, respectively. 14 O) k1 The polyoxyalkylene chain represented by (R 15 O) k3 The polyoxyalkylene chains represented by are preferably copolymer chains containing an oxyethylene group (a structural unit represented by the above formula (2)) and an oxypropylene group (a structural unit represented by the above formula (3)).

[0093] In each of the above-mentioned embodiments, the number of oxyalkylene groups in the polyoxyalkylene chain is preferably 100 or more. When the number of oxyalkylene groups in the polyoxyalkylene chain is 100 or more, the elongation of the heat insulating layer 101 is further improved by lengthening the main chain of the compound represented by formula (1), and the strength of the heat insulating layer 101 can also be improved. The number of oxyalkylene groups corresponds to m in formula (1-2), n in formula (1-3), and k1 and k3 in formula (1-4).

[0094] The number of oxyalkylene groups in the polyoxyalkylene chain is more preferably 130 or more, 180 or more, 200 or more, 220 or more, 250 or more, 270 or more, 300 or more, or 320 or more. The number of oxyalkylene groups in the polyoxyalkylene chain may be 600 or less, 570 or less, or 530 or less.

[0095] From the viewpoint that the heat insulating layer 101 has low elasticity and excellent elongation, the weight average molecular weight of the compound represented by formula (1) is preferably 5000 or more, 6000 or more, 7000 or more, 8000 or more, 9000 or more, 10000 or more, 11000 or more, 12000 or more, 13000 or more, 14000 or more, or 15000 or more. The weight average molecular weight of the compound represented by formula (1) is preferably 100000 or less, 80000 or less, 60000 or less, 34000 or less, 31000 or less, or 28000 or less.

[0096] The matrix polymer may contain only the compound represented by formula (1) as a monomer unit. The matrix polymer may further contain other polymerizable compounds (details will be described later) other than the compound represented by formula (1) as a monomer unit. At this time, from the viewpoint that the thermal insulation layer 101 is lower elastic and excellent in elongation, relative to the total of the compound represented by formula (1) and other polymerizable compounds (hereinafter referred to as "the total content of the monomer unit") 100 parts by mass, the content of the compound represented by formula (1) is preferably 20 parts by mass or more, 30 parts by mass or more, or 40 parts by mass or more. Relative to the total of 100 parts by mass of the content of the monomer unit, the content of the compound represented by formula (1) can be 80 parts by mass or less, 70 parts by mass or less, or 60 parts by mass or less.

[0097] Other polymerizable compounds (monomer units) in the matrix polymer may be, for example, compounds having a (meth)acryloyl group. As examples of such compounds, compounds having a (meth)acryloyl group that can be contained as monomer units in the acrylic copolymers described later may be cited. Furthermore, other polymerizable compounds in the matrix polymer may be compounds having, in addition to a (meth)acryloyl group, an aromatic hydrocarbon group, a group containing a polyoxyalkylene chain, an alkoxy group, a phenoxy group, a group containing a silyl group, a group containing a siloxane bond, a halogen atom, an amino group or an epoxy group. In particular, the matrix polymer contains, in addition to the (meth)acryloyl group, a compound having a hydroxyl group, a carboxyl group, an amino group or an epoxy group, thereby further improving the adhesion of the thermal insulation layer 101 to other components.

[0098] Examples of the compound having a (meth)acryloyl group and an aromatic hydrocarbon group include benzyl (meth)acrylate and the like.

[0099] Examples of the compound having a (meth)acryloyl group and a polyoxyalkylene chain-containing group include polyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, polybutylene glycol (meth)acrylate, and methoxypolybutylene glycol (meth)acrylate.

[0100] Examples of the compound having a (meth)acryloyl group and an alkoxy group include 2-methoxyethyl acrylate and the like.

[0101] As a compound which has a (meth)acryloyl group and a phenoxy group, phenoxyethyl (meth)acrylate etc. are mentioned.

[0102] Examples of the compound having a (meth)acryloyl group and a silyl group-containing group include 3-acryloxypropyltriethoxysilane, 10-methacryloxydecyltrimethoxysilane, 10-acryloxydecyltrimethoxysilane, 10-methacryloxydecyltriethoxysilane, and 10-acryloxydecyltriethoxysilane.

[0103] As a compound which has a (meth)acryloyl group and a siloxane bond-containing group, siloxane (meth)acrylate etc. are mentioned.

[0104] Examples of the compound having a (meth)acryloyl group and a halogen atom include trifluoromethyl (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 1,1,1,3,3,3-hexafluoro-2-propyl (meth)acrylate, perfluoroethyl methyl (meth)acrylate, perfluoropropyl methyl (meth)acrylate, perfluorobutyl methyl (meth)acrylate, perfluoropentyl methyl (meth)acrylate, perfluorohexyl methyl (meth)acrylate, perfluoroheptyl methyl (meth)acrylate, perfluorooctyl methyl (meth)acrylate, perfluorononyl methyl (meth)acrylate, perfluorodecyl methyl (meth)acrylate, perfluoroundecyl methyl (meth)acrylate, perfluorododecyl methyl (meth)acrylate, and perfluorobutyl methyl (meth)acrylate. (Meth)acrylates having fluorine atoms, such as perfluorotridecylmethyl (meth)acrylate, perfluorotetradecylmethyl (meth)acrylate, 2-(trifluoromethyl)ethyl (meth)acrylate, 2-(perfluoroethyl)ethyl (meth)acrylate, 2-(perfluoropropyl)ethyl (meth)acrylate, 2-(perfluorobutyl)ethyl (meth)acrylate, 2-(perfluoropentyl)ethyl (meth)acrylate, 2-(perfluorohexyl)ethyl (meth)acrylate, 2-(perfluoroheptyl)ethyl (meth)acrylate, 2-(perfluorooctyl)ethyl (meth)acrylate, 2-(perfluorononyl)ethyl (meth)acrylate, 2-(perfluorotridecyl)ethyl (meth)acrylate, and 2-(perfluorotetradecyl)ethyl (meth)acrylate.

[0105] Examples of the compound having a (meth)acryloyl group and an amino group include N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, and N,N-diethylaminopropyl (meth)acrylate.

[0106] Examples of the compound having a (meth)acryloyl group and an epoxy group include glycidyl (meth)acrylate, α-ethyl glycidyl (meth)acrylate, α-n-propyl glycidyl (meth)acrylate, α-n-butyl glycidyl (meth)acrylate, 3,4-epoxybutyl (meth)acrylate, 4,5-epoxypentyl (meth)acrylate, 6,7-epoxyheptyl (meth)acrylate, α-ethyl (meth)acrylate-6,7-epoxyheptyl (meth)acrylate, 3-methyl-3,4-epoxybutyl (meth)acrylate, 4-methyl-4,5-epoxypentyl (meth)acrylate, 5-methyl-5,6-epoxyhexyl (meth)acrylate, β-methyl glycidyl (meth)acrylate, and α-ethyl (meth)acrylate-β-methyl glycidyl.

[0107] The matrix polymer may contain one or more of the above-mentioned other polymerizable compounds as a monomer unit, and may further contain a compound represented by formula (1) or may not contain it.

[0108] The content of the matrix polymer based on the total mass of the heat insulating layer 101 may be, for example, 40 mass % or more, 50 mass % or more, 60 mass % or more, or 70 mass % or less, or 95 mass % or less or 90 mass % or less.

[0109] The heat insulating layer 101 may further contain other additives as needed. Examples of other additives include plasticizers, antioxidants (e.g., phenolic antioxidants), surface modifiers (e.g., silane coupling agents), dispersants, curing accelerators, colorants, crystal nucleating agents, thermal stabilizers, foaming agents, flame retardants, vibration dampers, dehydrating agents, flame retardant aids (e.g., metal oxides), etc. Based on the total mass of the heat insulating layer 101, the content of other additives may be 0.1% by mass or more, or 30% by mass or less.

[0110] The thickness of the heat insulating layer 101 may be, for example, 100 μm or more, 200 μm or more, or 500 μm or less, or 10 mm or less, 5 mm or less, or 2 mm or less.

[0111] The pressure-sensitive adhesive layer 102 may include a known pressure-sensitive adhesive. For example, the pressure-sensitive adhesive layer 102 may include an acrylic pressure-sensitive adhesive, an epoxy pressure-sensitive adhesive, etc. The acrylic pressure-sensitive adhesive may include, for example, an acrylic copolymer and a cross-linking agent.

[0112] The acrylic copolymer is a copolymer of two or more polymerizable compounds. The two or more polymerizable compounds include one or more compounds having a (meth)acryloyl group. The acrylic copolymer includes one or more compounds having a (meth)acryloyl group as monomer units, but may also include two or more, three or more, or four or more compounds having a (meth)acryloyl group as monomer units.

[0113] The compound having a (meth)acryloyl group may be, for example, an alkyl (meth)acrylate. The alkyl group (the alkyl part other than the (meth)acryloyl group) in the alkyl (meth)acrylate may be linear, branched, or cyclic. The number of carbon atoms in the alkyl group may be, for example, 1 to 30. The number of carbon atoms in the alkyl group may be 2 or more, 3 or more, or 25 or less, 20 or less, 15 or less, 10 or less, 7 or less, or 5 or less.

[0114] Examples of the compound having a (meth)acryloyl group include (meth)acrylic acid alkyl esters having a linear alkyl group having 1 to 11 carbon atoms, (meth)acrylic acid alkyl esters having a branched alkyl group having 1 to 11 carbon atoms, compounds having a (meth)acryloyl group and a heterocyclic ring-containing group, compounds having a (meth)acryloyl group and a hydroxyl group, and compounds having a (meth)acryloyl group and a carboxyl group.

[0115] As the (meth)acrylic acid alkyl ester having a linear alkyl group with 1 to 11 carbon atoms, methyl (meth)acrylate, butyl (meth)acrylate, etc. can be mentioned. As the (meth)acrylic acid alkyl ester having a branched alkyl group with 1 to 11 carbon atoms, 2-ethylhexyl (meth)acrylate, etc. can be mentioned. As the compound having a (meth)acryloyl group and a heterocyclic ring-containing group, N-acryloylmorpholine (ACMO) and the like can be mentioned. As the compound having a (meth)acryloyl group and a hydroxyl group, 2-hydroxyethyl (meth)acrylate and the like can be mentioned. As the compound having a (meth)acryloyl group and a carboxyl group, (meth)acrylic acid and the like can be mentioned.

[0116] The acrylic copolymer may contain other polymerizable compounds other than the compound having a (meth)acryloyl group as monomer units. Examples of other polymerizable compounds (monomer units) in the acrylic copolymer include acrylonitrile.

[0117] The weight average molecular weight (Mw) of the acrylic copolymer may be 50,000 or more, 100,000 or more, or 200,000 or more, or 1.2 million or less, 1.1 million or less, or 1 million or less.

[0118] The content of the acrylic copolymer may be 70% by mass or more, or 98% by mass or less, or 95% by mass or less, based on the total mass of the pressure-sensitive adhesive layer 102 .

[0119] The crosslinking agent may be, for example, a crosslinking agent having an epoxy group, a crosslinking agent having an isocyanate group, etc. The crosslinking agent having an epoxy group may have 2 or more, 3 or more, or 4 or more epoxy groups. Examples of crosslinking agents having 4 epoxy groups include N,N,N',N'-tetraglycidyl-1,3-bis(aminomethyl)cyclohexane and N,N,N',N'-tetraglycidyl-m-xylene diamine.

[0120] The crosslinking agent having an isocyanate group may have two or more isocyanate groups or three or more isocyanate groups. An example of a crosslinking agent having three isocyanate groups is "CORONATE L" (manufactured by TOSOH CORPORATION).

[0121] The thickness of the pressure-sensitive adhesive layer 102 may be, for example, 5 μm or more or 10 μm or more, or 200 μm or less, 100 μm or less, or 50 μm or less.

[0122] like Figure 1 In one embodiment shown, the sheet 100 may be composed only of the heat insulating layer 101 and the pressure sensitive adhesive layer 102. In another embodiment, the sheet may also have other layers in addition to the heat insulating layer and the pressure sensitive adhesive layer. In this case, in the sheet, the heat insulating layer and the pressure sensitive adhesive layer may contact each other (may not be stacked via other layers), and the heat insulating layer and the pressure sensitive adhesive layer may also be stacked via other layers. As examples of other layers, a surface protection layer, an adhesive layer, and a support layer may be cited.

[0123] In one embodiment, the sheet material having other layers may be a sheet material having a surface protection layer (first surface protection layer), a heat insulating layer, an adhesive layer (first adhesive layer), a support layer (first support layer), an adhesive layer (second adhesive layer), a support layer (second support layer), a pressure-sensitive adhesive layer and a surface protection layer (second surface protection layer). The surface protection layer may be, for example, composed of a resin film (PET film, etc.) having a surface in contact with the heat insulating layer or the pressure-sensitive adhesive layer and subjected to an easy-to-peel treatment. The adhesive layer may contain, for example, an acrylic adhesive, an epoxy adhesive, etc. The support layer may be, for example, composed of a resin film (polyimide film, etc.).

[0124] The thickness of the sheet 100 may be, for example, 100 μm or more, 200 μm or more, or 500 μm or less, or 11 mm or less, 5 mm or less, 3 mm or less, or 2 mm or less.

[0125] The sheet 100 can be manufactured, for example, by separately manufacturing the heat insulating layer 101 and the pressure sensitive adhesive layer 102, and bonding the heat insulating layer 101 to the pressure sensitive adhesive layer 102. For example, the manufacturing method of the sheet having the above-mentioned other layers may include: the steps of separately preparing a laminate A of a surface protective layer (first surface protective layer) and a heat insulating layer, a laminate B of an adhesive layer (first adhesive layer), a support layer (first support layer) and an adhesive layer (second adhesive layer), and a laminate C of a support layer (second support layer), a pressure sensitive adhesive layer and a surface protective layer (second surface protective layer); and the steps of bonding the heat insulating layer of the laminate A to the adhesive layer (first adhesive layer) of the laminate B, and bonding the adhesive layer (second adhesive layer) of the laminate B to the support layer (second support layer) of the laminate C.

[0126] The laminate A is obtained, for example, by the following method: after preparing the above-mentioned first hollow particles, the second hollow particles and a mixture containing a polymerizable compound, the polymerizable compound in the mixture is polymerized on the surface protective layer (first surface protective layer) to form a matrix polymer. As laminate B, for example, a double-sided adhesive tape having a support layer (first support layer) and an adhesive layer (first adhesive layer) and an adhesive layer (second adhesive layer) respectively arranged on both sides of the support layer can be used. Laminate C is obtained, for example, by the following method: a pressure-sensitive adhesive composition obtained by mixing materials such as acrylic pressure-sensitive adhesives is applied to the surface protective layer (second surface protective layer), and after the pressure-sensitive adhesive composition is dried and / or the curing component in the pressure-sensitive adhesive composition is cured to form a pressure-sensitive adhesive layer, a support layer (second support layer) is arranged on the surface of the pressure-sensitive adhesive layer on the opposite side of the surface protective layer (second surface protective layer). In the process of laminating laminate A, laminate B and laminate C, for example, a roll laminator can be used.

[0127] The sheet 100 described above has excellent releasability after the reflow process and can be suitably used as a heat insulating material in the reflow process. The sheet 100 can be a sheet used as a heat insulating material in the reflow process when manufacturing a semiconductor device.

[0128] <Method for manufacturing semiconductor device>

[0129] Another embodiment of the present invention is a method for manufacturing a semiconductor device, comprising: a step of placing a sheet on a semiconductor device; a step of reflowing the semiconductor device on which the sheet is placed; and a step of peeling the sheet from the semiconductor device.

[0130] Figure 2 2 is a schematic cross-sectional view showing one embodiment of the configuration process. Figure 2As shown, a semiconductor device (also referred to as a semiconductor package) 1A used in the configuration process includes, for example, a substrate 2, a lead 4 connected to the substrate 2 by solder (solder paste) 3, and a semiconductor chip 6 connected to the lead 4 via a wire 5. The semiconductor chip 6 is mounted on a die pad 8 via a die attach material 7 and is covered by a sealing material 9.

[0131] The sheet is arranged on at least a portion of the surface of the semiconductor device 1A. In one embodiment, the sheet 10 is arranged on the semiconductor device 1A so as to cover the entire surface of the sealing material 9. In another embodiment, the sheet 10 may be arranged so as to cover a portion of the surface of the sealing material 9 (for example, only the upper surface).

[0132] Figure 3 2 is a schematic cross-sectional view showing another embodiment of the configuration process. Figure 3 As shown, in another embodiment, a semiconductor device 11A used in the configuration step includes, for example, a substrate 12; an interposer 14 connected to the substrate 12 by means of solder (solder balls) 13; and a semiconductor chip 16 connected to the interposer 14 via an adhesive 15. The semiconductor chip 16 is connected to the interposer 14 via a plurality of protruding electrodes (bumps) 16a. The semiconductor chip 16 is covered by a sealing material 17 configured on the interposer 14.

[0133] In one embodiment, the sheet 18 is arranged on the semiconductor device 11A so as to cover the entire surface of the sealing material 17 and the entire side surface where the solder (solder ball) 13 and the interposer 14 are arranged.

[0134] As Figure 3 In another embodiment of the configuration process shown, the sheet 18 can be configured to cover only the entire surface of the sealing material 17 and the side of the place where the intermediate layer 14 is configured (it may not be configured on the side of the place where the solder (solder ball) 13 is configured). In another embodiment, the sheet 18 can be configured to cover only the entire surface of the sealing material 17, or it can be configured to cover only a portion of the surface of the sealing material 17 (for example, the upper surface). Even in these cases, the semiconductor device can be properly protected from the heat in the reflow process. However, for example, in the case where a low-temperature solder is used as the solder (solder ball) 13, from the viewpoint of protecting the solder (solder ball) 13 from the excessive heat in the reflow process and suppressing damage to the joint portion based on the solder, as Figure 3 As shown, the sheet 18 is preferably arranged so as to cover the entire surface of the sealing material 17 and the entire side surface where the solder (solder ball) 13 and the interposer 14 are arranged.

[0135] In another embodiment, a plurality of semiconductor devices (semiconductor packages) may be mounted on one substrate 2, 12, and a part or all of the plurality of semiconductor devices may be the above-mentioned semiconductor devices 1A, 11A. In the case where a part of the plurality of semiconductor devices is the above-mentioned semiconductor devices 1A, 11A, the remaining semiconductor devices may be semiconductor devices that are more heat-resistant (higher heat resistance) than the above-mentioned semiconductor devices 1A, 11A, and the solder in the remaining semiconductor devices is solder that is joined at a higher temperature than the solder 3, 13 in the above-mentioned semiconductor devices 1A, 11A. In this way, when a plurality of semiconductor devices (semiconductor packages) having different heat resistance are mounted on one substrate 2, 12, by arranging the sheets 10, 18 on the semiconductor devices 1A, 11A that are less heat-resistant (lower heat resistance), a plurality of semiconductor devices (semiconductor packages) having different heat resistance can be provided to the reflow process at one time.

[0136] In another embodiment, the sheet may be disposed on the surface of the substrate opposite to the surface on which the semiconductor chip is mounted. Figure 4 Yes means Figure 2 A schematic cross-sectional view of another embodiment of the configuration process shown. Figure 4 As shown, the sheet 10 is also arranged on the surface of the substrate 2 opposite to the surface on which the semiconductor chip 6 is mounted. Figure 5 Yes means Figure 3 A schematic cross-sectional view of another embodiment of the configuration process shown. Figure 5 As shown, the sheet 18 is also arranged on the surface of the substrate 12 opposite to the surface on which the semiconductor chip 16 is mounted. In these embodiments, for example, when a plurality of semiconductor devices (semiconductor packages) having different heat resistance are mounted on one substrate 2 or 12, by arranging more sheets 10 or 18 on the semiconductor devices 1B or 11B that are less heat-resistant (have low heat resistance), a plurality of semiconductor devices (semiconductor packages) having different heat resistance can be subjected to a reflow process at one time.

[0137] In the placement step, the sheet is preferably placed so that the surface of the semiconductor device (semiconductor package) contacts the pressure-sensitive adhesive layer of the sheet. In the placement step, the method of placing the sheet may include a pressing step of pressing the sheet onto the semiconductor device (semiconductor package) under vacuum or atmospheric pressure.

[0138] Specifically, in the crimping process, for example, first in the chamber of a vacuum laminator (for example, "V-130" manufactured by Nikko-Materials Co., Ltd.), a buffer material (for example, a rubber sheet), a release film, a semiconductor device (semiconductor package), a sheet and a release film are overlapped in sequence. Then, on the basis of evacuating the chamber, the sheet is pressed in a manner that makes it close to the semiconductor device (semiconductor package), thereby enabling the sheet to be crimped to the semiconductor device (semiconductor package). As another specific example, first, a semiconductor device (semiconductor package), a sheet and a release film are overlapped in sequence on a support (for example, a stainless steel plate). Then, a roller laminator (for example, "VA-770H special laminator" manufactured by TAISEI LAMINATOR CO., LTD.) is inserted, and the sheet is pressed in a manner that makes it close to the semiconductor device (semiconductor package), thereby enabling the sheet to be crimped to the semiconductor device (semiconductor package).

[0139] In the reflow process following the placement process, the semiconductor device is reflowed by a known method. Specifically, for example, the semiconductor device is placed in a reflow furnace, the temperature in the furnace is gradually raised, and after reaching a maximum temperature of 240 to 260° C., the temperature is gradually lowered. As a result, the solder paste is sintered, and the wiring board and the substrate are electrically connected.

[0140] In the stripping process following the reflow process, the sheet is stripped from the semiconductor device. The stripping method is not particularly limited, and for example, it may be a method of stripping the sheet by attaching a pressure-sensitive adhesive film to the sheet and stretching the pressure-sensitive adhesive film. In addition, the stripping method may be, for example, a method of stripping the sheet by pressing a roller onto the sheet via a support film and winding the sheet together with the support film. As a support film, for example, a double-sided tape can be used. For stripping, a device such as a tape remover (for example, "OTR-600SA" manufactured by OHMIYA IND.CO.,LTD.) may be used.

[0141] Example

[0142] Hereinafter, the present invention will be described in more detail based on examples, but the present invention is not limited to these examples.

[0143] <Example 1>

[0144] [Synthesis of the compound represented by formula (1-5)]

[0145] A 500 mL flask consisting of a stirrer, a thermometer, a nitrogen inlet pipe, a discharge pipe and a heating jacket was used as a reactor, and 225 g of a diol having a polyoxyalkylene chain ("NEWPOL 75H-90000" manufactured by SANYO CHEMICAL INDUSTRIES, LTD.) and 300 g of toluene were added to the reactor, stirred at 45°C and a stirring speed of 250 times / min, and nitrogen was flowed at 100 mL / min, and stirred for 30 minutes. Then, the temperature was lowered to 25°C, and after the temperature was lowered, 2.9 g of acryloyl chloride was added dropwise to the reactor and stirred for 30 minutes. Then, 3.8 g of triethylamine was added dropwise and stirred for 2 hours. Then, the temperature was raised to 45°C and the reaction was carried out for 2 hours. The reaction liquid was filtered and the filtrate was desolventized to obtain a compound represented by formula (1-5) (weight average molecular weight: 15000, m1+m2 in formula (1-5) is approximately 252±5, n1+n2 is approximately 63±5 integers (wherein m1, m2, n1 and n2 are respectively integers greater than 2, m1+n1≥100, m2+n2≥100) mixture, viscosity at 25°C: 50 Pa·s).

[0146]

[0147] [In formula (1-5), -r- represents the symbol of random copolymerization.]

[0148] [Production of thermal insulation layer]

[0149] 39.2 mass% of the compound represented by the formula (1-5), 23.5 mass% of dicyclopentanyl acrylate ("FANCRYL (registered trademark) FA-513A" manufactured by Showa Denko Materials Co., Ltd.), 15.7 mass% of 4-hydroxybutyl acrylate (manufactured by OSAKA ORGANIC CHEMICAL INDUSTRY LTD.), 11.0 mass% of first hollow particles ("MATSUMOTO MICROSPHERE (registered trademark) FN-190SSD" manufactured by Matsumoto Yushi-Seiyaku Co., Ltd., average particle size: 10 to 15 μm, maximum volume expansion ratio: 50 times or more, expansion start temperature: 190° C., maximum expansion temperature: 210 to 220° C.), and 11.0 mass% of second hollow particles (Japan Fillite "Expancel (registered trademark) 920DE80d30" manufactured by Co., Ltd., average particle size 60 to 90 μm, density 30 ± 3 kg / m 3, maximum volume expansion ratio: less than 5 times, shrinkage start temperature: 200°C) 5.8% by mass, polymerization initiator ("PERBUTYL (registered trademark) O" manufactured by NOF CORPORATION) 0.9% by mass, phenolic antioxidant ("Irganox 1010" manufactured by BASF Japan Ltd.) 3.1% by mass and surface conditioner ("BYK (registered trademark) 350" manufactured by BYK Co., Ltd.) 0.8% by mass were mixed to obtain a composition for making a heat insulating layer. In addition, based on the total amount of the composition for making a heat insulating layer, the amount of the first hollow particles was 3.8% by volume, and the amount of the second hollow particles was 67.3% by volume.

[0150] Two groups of molded plates with the demolding surface facing up of a demolding polyester sheet ("A31" manufactured by TOYOBO CO., LTD.) with a length of 200 mm × a width of 200 mm × a thickness of 5 mm were prepared on a glass plate with a length of 200 mm × a width of 200 mm × a thickness of 0.1 mm. A silicone rubber mold frame (200 mm × 200 mm) with a hole of 120 mm × 120 mm × 2.0 mm was set on the demolding surface of one molding plate, and the composition for making a heat insulating layer was filled on the inside of the mold frame. In addition, the demolding surface of another molding plate was set to the composition side, and after covering the upper cover, it was heated at 135°C for 40 minutes. Then, a molding plate, a silicone rubber mold frame, and a glass plate in another molding plate were removed to produce a laminate (laminate A) of a surface protective layer (polyester sheet) and an insulation layer (thickness 2.0 mm). In addition, the insulation layer was obtained by peeling off the surface protective layer of laminate A. The initial thermal conductivity of the heat insulating layer measured by the method described later was 63 mW / (m·K), and the thermal conductivity after heating was 67 mW / (m·K).

[0151] [Preparation of pressure-sensitive adhesive layer]

[0152] As monomer units, an acrylic copolymer resin (weight average molecular weight: 200,000) containing methyl acrylate (MA), 2-ethylhexyl acrylate (EHA), acrylic acid (AA), and 2-hydroxyethyl acrylate (HEA) at a ratio of MA:EHA:AA:HEA=50:40:0.5:9.5 on a mass basis was used. 100 parts by mass of an ethyl acetate solution of the acrylic copolymer resin (solid content: 35% by mass), 5 parts by mass of an isocyanate (trade name: CORONATE L, manufactured by TOSOH CORPORATION) as a crosslinking agent, 7 parts by mass of a 10-functional urethane acrylate (trade name: U-10PPA, manufactured by SHIN-NAKAMURA CHEMICAL Co., Ltd.) as a photocurable resin, and 0.21 parts by mass of a photopolymerization initiator (trade name: Irgcure 819, manufactured by BASF) were dissolved in a mixed solvent of toluene and methyl ethyl ketone so that the solid content was 25% by mass. Next, the mixture was stirred at a rotation speed of 1000 rpm for 5 minutes using an autorotation and revolution stirrer, and then left to stand at room temperature until bubbles disappeared, thereby obtaining a pressure-sensitive adhesive composition.

[0153] The obtained pressure-sensitive adhesive composition was applied to the easily releasable surface of a 38 μm thick polyester film (trade name: PUREX A31, manufactured by TOYOBO CO., LTD.) having one side subjected to an easily releasable treatment using a silicone release agent, and then dried in a drying oven at 100° C. for 2 minutes and at 300 mJ / cm 2 Irradiate ultraviolet light with a wavelength of 365nm, thereby curing the photocurable resin to form a pressure-sensitive adhesive layer with a thickness of 10μm. Then, at room temperature (25°C), a polyimide film substrate with a thickness of 25μm (trade name: KAPTON 100H, manufactured by DUPONT-TORAY CO., LTD.) is laminated on the exposed surface of the formed pressure-sensitive adhesive layer, thereby preparing a laminate (laminate C) in which a surface protective layer (polyester film), a pressure-sensitive adhesive layer and a support layer (polyimide film substrate) are laminated in sequence. In addition, by peeling off the surface protective layer of laminate C, a pressure-sensitive adhesive layer with a support layer is obtained. Regarding the pressure-sensitive adhesive layer, the initial 90° peel strength measured by the method described later is 7N / m.

[0154] [Sheet production]

[0155] Using a roll laminator (HOTDOG LMP-350EX manufactured by LAMI CORPORATION INC.), an adhesive tape (a tape having a support layer and adhesive layers provided on both sides of the support layer. Manufactured by ShowaDenko Materials Co., Ltd., Hi-Bon 11-652) was laminated on the support layer side of the laminate C. Then, using the roll laminator, the laminate A was laminated on the tape in such a manner that the tape was in contact with the heat insulating layer, thereby obtaining the sheet material involved in Example 1. The thickness of the sheet material involved in Example 1 was 2135 μm.

[0156] <Example 2>

[0157] A sheet material according to Example 2 was obtained in the same manner as in Example 1 except that carbon felt ("Carbon Felt F-350" manufactured by Asahi Sangyo Co., Ltd., thickness: 2.8 mm) was used as the heat insulating layer and the heat insulating layer was used instead of the laminate A. The heat insulating layer used in Example 2 had an initial thermal conductivity of 61 mW / (m·K) and a heat conductivity of 53 mW / (m·K) after heating as measured by the method described below. The thickness of the sheet material according to Example 2 was 2935 μm.

[0158] <Example 3>

[0159] In the preparation of the heat insulating layer, the sheet material of Example 3 was obtained in the same manner as in Example 1 except that the composition for preparing the heat insulating layer was changed to the composition for preparing the heat insulating layer as described below. 35.19 mass % of the compound represented by formula (1-5), 21.12 mass % of dicyclopentyl acrylate ("FANCRYL (registered trademark) FA-513A" manufactured by Showa Denko Materials Co., Ltd.), 14.08 mass % of 4-hydroxybutyl acrylate (manufactured by OSAKA ORGANIC CHEMICAL INDUSTRY LTD.), inorganic hollow particles ("Q-CEL 5020" manufactured by Potters-Ballotini Co., Ltd., with an average particle size of 60 μm and a density of 0.20 g / cm 3) 25.21 mass %, a polymerization initiator ("PERBUTYL (registered trademark) O" manufactured by NOFCORPORATION) 0.84 mass %, a phenolic antioxidant ("Irganox 1010" manufactured by BASF Japan Ltd.) 2.82 mass % and a surface conditioner ("BYK (registered trademark) 350" manufactured by BYK Co., Ltd.) 0.74 mass % were mixed to obtain a composition for preparing a thermal insulation layer. In addition, based on the total amount of the composition for preparing a thermal insulation layer, the amount of inorganic hollow particles added was 63 volume %. Regarding the thermal insulation layer used in Example 3, the initial thermal conductivity measured by the method described later was 130 mW / (m·K), and the thermal conductivity after heating was 125 mW / (m·K). The thickness of the sheet involved in Example 3 is 2135 μm.

[0160] <Example 4>

[0161] As the heat insulating layer, a melamine sponge ("Basotect G+" manufactured by INOAC CORPORATION CO., LTD, thickness: 2.5 mm) was used, and the sheet material involved in Example 4 was obtained in the same manner as in Example 1, except that the heat insulating layer was used instead of the laminate A. The initial thermal conductivity of the heat insulating layer used in Example 4 measured by the method described later was 35 mW / (m·K), and the thermal conductivity after heating was 38 mW / (m·K). The thickness of the sheet material involved in Example 4 was 2635 μm.

[0162] <Example 5>

[0163] As the heat insulating layer, glass fiber paper ("SB-150TS" manufactured by Oribest Co., Ltd., thickness: 0.95 mm) was used, and the sheet material involved in Example 5 was obtained in the same manner as in Example 1, except that the heat insulating layer was used instead of the laminate A. The initial thermal conductivity of the heat insulating layer used in Example 5 measured by the method described below was 43 mW / (m·K), and the thermal conductivity after heating was 40 mW / (m·K). The thickness of the sheet material involved in Example 5 was 1085 μm.

[0164] <Comparative Example 1>

[0165] As the heat insulating layer, a glass felt ("heat-resistant glass felt B" manufactured by A&A Material Corporation, thickness: 5 mm) was used, and the sheet material involved in Comparative Example 1 was obtained in the same manner as in Example 1, except that the heat insulating layer was used instead of the laminate A. The initial thermal conductivity of the heat insulating layer used in Comparative Example 1 measured by the method described below was 35 mW / (m·K), and the thermal conductivity after heating was 37 mW / (m·K). The thickness of the sheet material involved in Comparative Example 1 was 5135 μm.

[0166] <Example 6>

[0167] In the preparation of the pressure-sensitive adhesive layer, instead of the above-mentioned acrylic copolymer resin, an acrylic copolymer resin (weight average molecular weight: 200,000) containing 2-ethylhexyl acrylate (EHA) and 2-hydroxyethyl acrylate (HEA) in a ratio of EHA:HEA=65:35 on a mass basis was used as a monomer unit, and the sheet involved in Example 6 was obtained in the same manner as in Example 1. Regarding the pressure-sensitive adhesive layer, the initial 90° peel strength measured by the method described later was 38N / m. The thickness of the sheet involved in Example 6 was 2135μm.

[0168] <Example 7>

[0169] A sheet according to Example 7 was obtained in the same manner as in Example 6 except that the same carbon felt as in Example 2 ("Carbon Felt F-350" manufactured by Asahi Sangyo Co., Ltd., thickness: 2.8 mm) was used as the heat insulating layer instead of the laminate A. The thickness of the sheet according to Example 7 was 2935 μm.

[0170] <Example 8>

[0171] A sheet material according to Example 8 was obtained in the same manner as in Example 6, except that the same heat insulating layer as in Example 3 was used as the heat insulating layer. The thickness of the sheet material according to Example 8 was 2135 μm.

[0172] <Comparative Example 2>

[0173] A sheet according to Comparative Example 2 was obtained in the same manner as in Example 6 except that the same melamine sponge as in Example 4 ("Basotect G+" manufactured by INOAC CORPORATION CO., LTD., thickness: 2.5 mm) was used as the heat insulating layer instead of the laminate A. The thickness of the sheet according to Comparative Example 2 was 2635 μm.

[0174] <Comparative Example 3>

[0175] A sheet material according to Comparative Example 3 was obtained in the same manner as in Example 6 except that the same glass fiber paper ("SB-150TS" manufactured by Oribest Co., Ltd., thickness: 0.95 mm) as in Example 5 was used as the heat insulating layer instead of the laminate A. The thickness of the sheet material according to Comparative Example 3 was 1085 μm.

[0176] <Comparative Example 4>

[0177] A sheet material according to Comparative Example 4 was obtained in the same manner as in Example 6 except that the heat insulating layer was replaced with the laminate A by using the same glass mat ("heat-resistant glass mat B" manufactured by A&A Material Corporation, thickness: 5 mm) as in Comparative Example 1. The thickness of the sheet material according to Comparative Example 4 was 5135 μm.

[0178] <Evaluation>

[0179] [Overall strength of the insulation layer after heating]

[0180] The overall strength after heating of the heat insulating layer used in each embodiment and comparative example was measured by the following procedure. Each heat insulating layer was cut into 20 mm × 50 mm, and a rectangular test piece of 20 mm (side x) × 50 mm (side y) × 2 mm (side z) was made. Each test piece was passed through a reflow oven (TNP25-337EM series N2 reflow device manufactured by TAMURA CORPORATION) to apply a thermal history, and then naturally cooled. Specifically, the thermal history was applied by heating from room temperature (25°C) to 200°C at a heating rate of 47°C / min in the reflow oven, and then heating from 200°C to 260°C at a heating rate of 38°C / min. And, specifically, natural cooling is cooling to 60°C in the reflow oven, taking it out of the reflow oven and cooling it to 25°C. Then, after the test piece was left to stand at 25°C for 24 hours, the overall strength of each insulation layer in the thickness direction at 25°C was measured using a tensile tester ("Autograph EZ-TEST EZ-S" manufactured by SHIMADZU CORPORATION). Specifically, first, a cut with a depth of 15 mm was made from the surface of each sample including the side x and the side z in a direction perpendicular to the side z using a cutter, thereby dividing one end of the test piece into two forks to form two ends. The two ends were clamped with the chucks of the tensile tester, respectively, and stretched under the conditions of a distance of 20 mm between the chucks and a tensile speed of 5 mm / min, and the magnitude of the force when the test piece broke was measured as the overall strength. The results are shown in Tables 1 and 2.

[0181] [Measurement of thermal conductivity of heat insulating layer]

[0182] The thermal conductivity of the heat insulating layer used in each example and comparative example was measured by the following procedure. The heat insulating layer was cut into 8 cm × 13 cm × 2.0 mm, sandwiched between a reference plate and a measuring probe, and the thermal conductivity (initial thermal conductivity) was measured at 25°C using a rapid thermal conductivity meter ("QTM-710" manufactured by KYOTO ELECTRONICS MANUFACTURING CO., LTD., measuring probe PD-11N, thin film measurement mode). In addition, a heat history was applied in the same manner as in the above-mentioned [Overall strength of the heat insulating layer after heating], and after natural cooling, the thermal conductivity (heating thermal conductivity) was measured in the same manner. For the reference sample, two release-treated polyester sheets ("A31" manufactured by TOYOBO CO., LTD.) were overlapped and sandwiched between a reference plate and a measuring probe for measurement.

[0183] [90° peel strength of pressure-sensitive adhesive layer]

[0184] The 90° peel strength of the pressure-sensitive adhesive layer used in each embodiment and comparative example was measured by the following procedure. A Si wafer with a length of 25 mm × a width of 70 mm and a pressure-sensitive adhesive layer with a support layer cut into a length of 20 mm × a width of 60 mm were prepared. A pressure-sensitive adhesive layer with a support layer was provided on the Si wafer so that the pressure-sensitive adhesive layer was in contact with the Si wafer and bubbles would not enter between the two. The Si wafer provided with a pressure-sensitive adhesive layer with a support layer was placed on a stainless steel plate with a length of 380 mm × a width of 500 mm × a thickness of 0.5 mm, and a roller laminator ("VA-770H special laminator" manufactured by TAISEI LAMINATOR CO., LTD.) was used at a pressure of 6 kgf / cm 2 , rotation speed 0.2rpm, temperature 40 ℃ conditions, affixed pressure-sensitive adhesive layer and Si wafer, thereby making a sample. The pressure-sensitive adhesive layer with support layer of the obtained sample was cut with a width of 5mm, peeled off 10mm on one side of the length direction from the Si wafer, and the 90° peel strength (initial 90° peel strength) was measured by a tensile tester ("Autograph EZ-TEST EZ-S" manufactured by SHIMADZU CORPORATION). In addition, after applying a thermal history to the sample in the same manner as the above-mentioned [overall strength of the insulation layer after heating] and cooling it naturally, the peel strength (90° peel strength after heating) was measured in the same manner. The results are shown in Tables 1 and 2.

[0185] [Sheet peelability]

[0186] The entire surface protective layer of the sheet of each example and comparative example was peeled off and the sheet was passed through a roll laminator ("VA-770H Special Laminator" manufactured by TAISEI LAMINATOR CO., LTD.) at a pressure of 6 kgf / cm 2 , a rotation speed of 0.2rpm, and a temperature of 40°C, a pressure-sensitive adhesive layer was pasted on a Si wafer in such a way that the pressure-sensitive adhesive layer was in contact with the Si wafer, thereby preparing a sample. The sample was subjected to the same thermal history as the above-mentioned [overall strength of the insulating layer after heating] and naturally cooled. Then, a single side (the surface where the adhesive layer is exposed) of a double-sided tape (a tape having a support layer and an adhesive layer arranged on both sides of the support layer. A release film is provided on one adhesive layer. "Hi-Bon 11-652" manufactured by Showa Denko Materials co., Ltd.) was attached to the insulating layer of the sheet. The release film on the other side of the double-sided tape is peeled off, and a roller is pressed on the surface of the double-sided tape to which the release film is attached, and it is wound up together with the double-sided tape, thereby peeling off the sheet. At this time, the evaluation was "OK" when the interface between the pressure-sensitive adhesive layer and the Si wafer was peeled off and the pressure-sensitive adhesive layer was peeled off together with the heat insulating layer, etc., and the evaluation was "NG" when the interface between the layers constituting the sheet was peeled off and a part of the sheet including the pressure-sensitive adhesive layer remained on the Si wafer. The results are shown in Tables 1 and 2.

[0187] [Table 1]

[0188]

[0189] [Table 2]

[0190]

[0191] Explanation of symbols

[0192] 1A, 1B, 11A, 11B-semiconductor device, 2, 12-substrate, 3-solder (solder paste), 4-lead, 5-conductor wire, 6, 16-semiconductor chip, 7-chip adhesive material, 8-chip pad, 9, 17-sealing material, 10, 18, 100-sheet, 13-solder (solder ball), 14-intermediate layer, 15-adhesive, 16a-protruding electrode, 101-insulating layer, 102-pressure-sensitive adhesive layer.

Claims

1. A sheet material comprising a heat insulating layer and a pressure-sensitive adhesive layer, The overall strength of the thermal insulation layer after a thermal history of heating from 25°C to 200°C at a heating rate of 47°C / min and then from 200°C to 260°C at a heating rate of 38°C / min is greater than the 90° peel strength of the pressure-sensitive adhesive layer after the thermal history. 2 . The sheet according to claim 1 , which is used as a heat insulating material in a reflow process when manufacturing a semiconductor device.

3. A method for manufacturing a semiconductor device, comprising: A step of configuring the sheet according to claim 1 or 2 on a semiconductor device; A step of performing reflow soldering on the semiconductor device provided with the sheet; and a step of peeling the sheet from the semiconductor device.

Citation Information

Patent Citations

  • Method of manufacturing magnetic recording apparatus and magnetic recording apparatus

    JP2017224663A